MIDDLE ENGLISH ANTIDOTARIUM NICHOLAI: EVIDENCE FOR LINGUISTIC DISTRIBUTION AND DISSEMINATION IN THE VERNACULAR - Carrillo Linares, Mª José (International Journal of English Studies, 2009)
The medieval treatise known as Antidotarium Nicholai is preserved in Middle English in several versions from at least five different manuscript families. The Latin version of this treatise was a requirement in the medical curriculum at medieval European universities. The purpose of this paper is to establish the provenance or distribution of the language in eight of the extant copies in order to arrive at a conclusion about the diffusion of this work. Analysed are the dialectal furins and features of the copies found in Clainbridge, Corpus Christi College 424, London, British Library Harley 2374, Glasgow, Uinversity Library Ferguson 147, Oxford, Bodleian Library Aslimole 1438, Cainbridge, Magdalene College Pepys 1307. Cainbridge, St. Jolin's College 37 and Glasgow, University Library Hunter 117. With this analysis I intend to determine the filial relationship ainong the different versions, and to locate each copy within a specific dialect aren.